Introducing sea level change - Dawson, A. G. (Dunedin Academic Press, 2018)
"One of the most important issues in current debates on climate change is sea level rise. Hardly a day goes by when there is not a newspaper article, TV or radio presentation on the topic. Almost half of the world's population live on or near the coast, so there is real concern about the impact that future sea level rise may have. Yet media predictions of future changes tend to be depicted in a sensationalist manner and quite often the explanations of scientific discoveries that have explained the patterns of sea level change that have taken place across the Earth since the end of the last ice age. Alastair Dawson introduces the many complex processes, some of which are not well-known, that influence patterns and rates of relative sea level change. Using this knowledge, the reader is much better placed to form a clearer perspective on what the future is likely to have in store for sea levels on Earth"--Page 4 of cover of print version
Keywords: Sea level.; Climatic changes.; elektronické knihy; electronic books